The Effect of Role Playing Methods on Social-emotional Development in Preschool Children - Marthalisa Wirahandayani; Windy Rakhmawati; Ema Arum Rukmasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Problems that are often experienced by preschool-age children include maladjustment, egocentric, aggressiveness, anxiety, and tend to withdraw from society so that it can cause behavioral problems that reduce social-emotional development. If this problem is not addressed immediately, it can have a negative impact on the health and behavior of children in adulthood. Provision of effective role playing encourages social emotional development of children where through fun playing activities, children get rich experiences so that they can improve social emotional development. This study aims to conduct a literature review review related to the influence of the role playing method on the social emotional development of preschool-aged children. The method used is SLR (Systematic Literature Review). Data collection was carried out by identifying, screening, eligibility, and inclusion stages. A total of 15 articles used in this study were obtained from the PubMed, Ebsco, Sage, and Science Direct databases. The results show that role play affects children's social emotional development. The role playing method can be the right solution for educators and parents in improving children's better social emotional development